Blood politics : race, culture, and identity in the Cherokee Nation of Oklahoma - Sturm, Circe, 1967- (ACLS Humanities E-Book., 2002)
Circe Sturm takes a bold and original approach to one of the most highly charged and important issues in the United States today: race and national identity. Focusing on the Oklahoma Cherokee, she examines how Cherokee identity is socially and politically constructed, and how that process is embedded in ideas of blood, color, and race.